Validation of a moral judgment instrument for Filipino students - Villanueva, Eva S. 1926-
The aim of the study is to determine the level of moral judgment of Filipino students. It is an attempt to validate the Exercise in Evaluating Issues (EEI), a moral judgment instrument constructed by the researcher for Filipino students, and patterned after the Defining Issues Test devised by Rest. The study also seeks to test the reliability and stability of the instrument, and to determine what signal and interacting factors among the selected variables of age, sex, education, type of school, father's education, mother's education, and residence, have significant influence on the moral judgment of the students. The researcher hopes that the study will help stimulate more interest in the cognitive-developmental approach to morality, which seemed to offer a more effective approach.